Predictors of new‐onset chronic kidney disease in patients managed surgically for T1a renal cell carcinoma: An Australian population‐based analysis. Issue 7 (22nd May 2018) - Ahn, Thomas; Ellis, Robert J.; White, Victoria M.; Bolton, Damien M.; Coory, Michael D.; Davis, Ian D.; Francis, Ross S.; Giles, Graham G.; Gobe, Glenda C.; Hawley, Carmel M.; Johnson, David W.; Marco, David J. T.; et al.
Abstract : Background: New‐onset chronic kidney disease (CKD) following surgical management of kidney tumors is common. This study evaluated risk factors for new‐onset CKD after nephrectomy for T1a renal cell carcinoma (RCC) in an Australian population‐based cohort. Methods: There were 551 RCC patients from the Australian states of Queensland and Victoria included in this study. The primary outcome was new‐onset CKD (eGFR <60 mL/min per 1.73 m 2 ) and the secondary outcome was new‐onset moderate‐severe CKD (<45 mL/min per 1.73 m 2 ). Multivariable logistic regression was used to evaluate associations between patient, tumor and health‐service characteristics and these outcomes. Results: Forty percent (219/551) of patients developed new‐onset CKD, and 12% (68/551) experienced new‐onset moderate‐severe CKD. Risk factors for new‐onset CKD were age, lower preoperative eGFR, tumor size >20 mm, radical nephrectomy, lower hospital caseloads (<20 cases/year), and rural place of residence. The associations between rural place of residence and low center volume were a consequence of higher radical nephrectomy rates. Conclusion: Risk factors for CKD after nephrectomy generally relate to worse baseline health, or likelihood of undergoing radical nephrectomy. Surgeons in rural centres and hospitals with low caseloads may benefit from formalized integration with specialist centers for continued professional development and case‐conferencing, to assist in management decisions.